Does timing matter? : Empirical Study on the Effects of First Equity Funding Timing in Deep-Tech Startups (Europe and North America, 2010–2020) - Mäkivirta, Henri (My University, 2025)
This study examines how well the timing between deep tech startup’s launch and first round of equity funding can predict the startup’s success outcome. The empirical study uses proprietary data of more than six thousand observations on European and U.S. deep tech startups founded between 2010 and 2020. The success in the study is defined by both binary and quantifiable outcomes. In binary outcomes, success is defined as an outcome where a startup has achieved a unicorn valuation (€1billion), been a subject to merger or acquisition of over €500M or raised funding over €100M in its lifetime. The valuation outcome uses the valuation of the startup’s latest funding round. The literary review of this thesis captures the theoretical foundations of venture capital. It covers how VC funding cycles work in general and how signaling theory plays a key role in each funding round. Deep tech startups’ unique funding dynamics are compared to more traditional software startups. This study also investigates the role of non-dilutive funding, which is important in research heavy deep tech innovation. The empirical study measures the impact of time between deep tech startup’s launch and first round of equity funding by using that time as a predictor variable to the outcome. This study uses logistic regression, linear regression and multiple regression to estimate the impact of each variable for predicting the success outcome. The results show that timing matter when predicting the binary outcome with logistic regression model. Logistic regression reveals that the probabilities for success are the highest when raising first round of funding three to eight months after the launch. When testing for a quantifiable outcome with linear regression and multiple regression, the timing effect disappears. Controlling other variables like patent, region and industry together with timing turn out to be more robust. The timing of the first equity funding round has a strong non-linear effect on whether a deep-tech startup achieves a successful outcome or not. However, the impact on valuation is mostly shaped by other factors than timing, such as how strong the startup’s IP is, where it is located, and what industry it operates in.

Tässä Pro Gradu -tutkielmassa tarkastellaan, kuinka hyvin syväteknologiayrityksen perustamisen ja ensimmäisen oman pääoman ehtoisen rahoituskierroksen välinen aika voi ennustaa startupin menestystä. Empiirisessä tutkimuksessa käytetään datana eurooppalaisia ja yhdysvaltalaisia syväteknologiayrityksiä, jotka on perustettu vuosina 2010–2020. Menestystä mitataan sekä binäärisellä että kvantitatiivisella mittarilla. Binäärisesti startup määritetään menestyksekkääksi, mikäli startup on saavuttanut yksisarvisen valuaation (1 miljardi euroa), ollut yli 500 miljoonan euron fuusion tai yritysoston kohteena tai kerännyt yhteensä yli 100 miljoonan euron rahoituksen elinkaarensa aikana. Valuaation pohjana käytetään startupin viimeisimmän rahoituskierroksen arvostusta. Kirjallisuuskatsaus kuvaa kasvuyritysten riskipääoman teoreettisia perusteita. Se käsittelee, miten riskipääomarahoitussyklit toimivat yleisesti ja miten signalointiteorialla on keskeinen rooli jokaisessa rahoituskierroksessa. Syväteknologiayritysten ainutlaatuista rahoitusdynamiikkaa verrataan perinteisempiin kasvuyrityksiin. Tutkimus tutkii myös apurahapohjaisen rahoituksen roolia, jolla on suuri merkitys syväteknologiainnovaatioiden kaupallistamisessa. Empiirinen tutkimus mittaa deep tech -startup-yrityksen perustamisen ja ensimmäisen rahoituskierroksen välisen ajan vaikutusta käyttämällä kyseistä aikaa ennustemuuttujana tulokselle. Tässä tutkimuksessa käytetään logistista regressiota ja lineaarista regressiota arvioidakseen kunkin muuttujan vaikutusta onnistumisen ennustamiseen. Tulokset osoittavat, että ajoituksella on merkitystä ennustettaessa binääristä lopputulosta logistisella regressiomallilla. Logistinen regressio paljastaa, että onnistumisen todennäköisyydet ovat suurimmat, kun ensimmäinen rahoituskierros kerätään 3–8 kuukautta perustamisen jälkeen. Kun testataan kvantifioitavaa lopputulosta lineaarisella regressiolla ja moninkertaisella regressiolla, ajoituksen vaikutus häviää. Muiden muuttujien, kuten patentin, alueen ja toimialan, kontrollointi yhdessä ajoituksen kanssa osoittautuu selittävän menestystä paremmin. Ensimmäisen rahoituskierroksen ajoituksella on voimakas epälineaarinen vaikutus siihen, saavuttaako deep tech -startup onnistuneen lopputuloksen vai ei. Onnistumiseen vaikuttavat kuitenkin enimmäkseen muut tekijät kuin ajoitus, kuten startupin immateriaalioikeuksien vahvuus, sijainti ja toimiala.
Keywords: deep tech, startups, funding timing, funding round, launch, venture capital, startup success, unicorn, valuation, patents, natural splines, logistic regression, linear regression, multiple regression